"POST-POSTSTRUCTURALIST" OR PRELAPSARIAN? CULTURAL STUDIES AND THE NEW HISTORICISM - Brantlinger, Patrick (Surfaces, 1992)
A comparison of New Historicism and Cultural Studies as contemporary theoretical approaches to the problem of cultural analysis.